Aplicación móvil multiplataforma de notificación de rutas de recolección de desechos del GADM Chone - Zambrano Zambrano, Cristhian Alfredo (2020)
The titling work consisted of providing a multiplatform tool to the Municipal Decentralized Autonomous Government of Chone canton that allows notification to citizens of the arrival of waste collectors. The system was developed using the Extreme Programming methodology, in planning, each of the user stories and the iterations for the estimation of development time were defined, in designing, the database, class diagram and interfaces were developed, in development the multiplatform application with the Ionic 4 framework according to what is established in the user stories and in the last phase unit tests were carried out to check the correct operation with the respective consumption of services (REST API). As a result, a mobile application was obtained that consumes geolocation services for waste collection vehicles and notifies users of their arrival, in addition to a web application that allows the administration and control of what will be provided in the mobile application